Difficulties of the Grade Four Pupils Towards Accomplishing Experiment-Based Learning Performance Tasks in Science in the New Normal - Carmela Santos (SEAMEO QITEP in Science, 2022)
This study determines the difficulties of the grade four pupils towards accomplishing experiment-based learning performance tasks in Science in Parsolingan Elementary School for the school year 2021-2022 with the new normal education. It employed a mixed method of quantitative-qualitative research design. In gathering the data, survey through a questionnaire was used. Arithmetic mean was used to treat the data gathered. Results showed that the greatest difficulty faced to the least were the Needed Materials (M= 3.79), Task Instructions (M=3.69), Completion Time (M=3.63), Home Environment (M=3.57), and Learning Support (M=3.30). These findings led to suggest that teachers shall consider seeking support from internal and external stakeholders for the provision of required materials for the experiment-based learning performance tasks in Science to help the grade four pupils in optimising the execution of experimental processes and skills needed.